Norm enforcement in the city: A natural field experiment - Loukas Balafoutas; Nikos Nikiforakis (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
Extensive evidence from laboratory experiments indicates that many individuals are willing to use costly punishment to enforce social norms, even in one-shot interactions. However, there appears to be little evidence in the literature of such behavior in the field. We study the propensity to punish norm violators in a natural field experiment conducted in the main subway station in Athens, Greece. The large number of passengers ensures that strategic motives for punishing are minimized. We study violations of two distinct efficiency enhancing social norms. In line with laboratory evidence, we find that individuals punish norm violators. Men are more likely than women to punish violators, while the decision to punish is unaffected by the violators height and gender. Interestingly, we find that violations of the better known of the two norms are substantially less likely to trigger punishment. We present additional evidence from two surveys providing insights into the determinants of norm enforcement.
Keywords: C93; D63; H41; 330; norm enforcement; social norms; field experiment; altruistic punishment; cooperation